CD8 cells of patients with diffuse cutaneous leishmaniasis display functional exhaustion: the latter is reversed, in vitro, by TLR2 agonists. - Joselín Hernández-Ruiz; Norma Salaiza-Suazo; Georgina Carrada; Sofía Escoto; Adriana Ruiz-Remigio; Yvonne Rosenstein; Alejandro Zentella; Ingeborg Becker (Public Library of Science (PLoS), 2010)
Leishmania mexicana (Lm) causes localized (LCL) and diffuse (DCL) cutaneous leishmaniasis. DCL patients have a poor cellular immune response leading to chronicity. It has been proposed that CD8 T lymphocytes (CD8) play a crucial role in infection clearance, although the role of CD8 cytotoxicity in disease control has not been elucidated. Lesions of DCL patients have been shown to harbor low numbers of CD8, as compared to patients with LCL, and leishmanicidal treatment restores CD8 numbers. The marked response of CD8 towards Leishmania parasites led us to analyze possible functional differences between CD8 from patients with LCL and DCL. We compared IFNγ production, antigen-specific proliferation, and cytotoxicity of CD8 purified from PBMC against autologous macrophages (MO) infected with Leishmania mexicana (MOi). Additionally, we analyzed tissue biopsies from both groups of patients for evidence of cytotoxicity associated with apoptotic cells in the lesions. We found that CD8 cell of DCL patients exhibited low cytotoxicity, low antigen-specific proliferation and low IFNγ production when stimulated with MOi, as compared to LCL patients. Additionally, DCL patients had significantly less TUNEL+ cells in their lesions. These characteristics are similar to cellular "exhaustion" described in chronic infections. We intended to restore the functional capacity of CD8 cells of DCL patients by preincubating them with TLR2 agonists: Lm lipophosphoglycan (LPG) or Pam3Cys. Cytotoxicity against MOi, antigen-specific proliferation and IFNγ production were restored with both stimuli, whereas PD-1 (a molecule associated with cellular exhaustion) expression, was reduced. Our work suggests that CD8 response is associated with control of Lm infection in LCL patients and that chronic infection in DCL patients leads to a state of CD8 functional exhaustion, which could facilitate disease spread. This is the first report that shows the presence of functionally exhausted CD8 T lymphocytes in DCL patients and, additionally, that pre-stimulation with TLR2 ligands can restore the effector mechanisms of CD8 T lymphocytes from DCL patients against Leishmania mexicana-infected macrophages.